Natural plant management and development in Sulaymaniyah Governorate - Hassan, Saad Sabah; Waheed, Hossam Kanaan (Al-Adab Journal, 2021)
Natural plant management and development is one of the main goals that the world strives to achieve because it is the backbone that supports most aspects of human life with what it needs from the elements of success, development and well-being. Important natural and finding appropriate solutions to these problems as well as addressing the impact of natural plants on the developmental processes in the province in order to highlight the most important aspects that enter the natural plant in its sustainability. This study revealed the presence of good types of natural plants growing in and in Sulaymaniyah Governorate, such as oak, pine and walnut forests, and riverbank trees such as willow and western, in addition to the steppe plants, both wet and dry, and others.